Assessment of the correlation between M23C6 precipitates and pitting corrosion resistance of 0Cr13 martensitic stainless steel. (15th August 2021) - Zhao, Yonggang; Liu, Wei; Zhang, Tianyi; Sun, Zongteng; Wang, Yabin; Fan, Yueming; Dong, Baojun
Highlights: The Volta potential of Cr-depleted regions was lower than that of steel matrix and the regions were dissolved preferentially. Increasing Cr contents in the Cr-depleted regions hampered the effect of Cr deficiency in the weak passive film. Low width and density of Cr-depleted regions reduced the intensity of pits on steel surface. High Cr contents and low Cr-depleted regions width and density led to good pitting corrosion resistance for 0Cr13 MSS. Abstract: The effect of M23 C6 precipitates on the pitting behavior of 0Cr13 martensitic stainless steel (MSS) was investigated. The results revealed that the precipitates in the 0Cr13 MSS with different tempering temperatures were all M23 C6 with a face-centered cubic (FCC) structure. The Cr-depleted regions had approximately 6 mV Volta potential lower than the steel matrix. The increasing Cr contents in the Cr-depleted regions hampered the effect of Cr deficiency in the weak passive film. The low width and density of Cr-depleted regions reduced the intensity of pits on steel surface. The pitting corrosion resistance was enhanced as the tempering temperature increased.